Molecular Analysis of Antimicrobial-Susceptible and -Resistant Escherichia coli from Retail Meats and Human Stool and Clinical Specimens in a Rural Community Setting - Hannah, Elizabeth Lyon (Mary Ann Liebert, Inc., 2009)
BACKGROUND: Foodborne antimicrobial-resistant Escherichia coli may colonize and cause infections in humans, but definitive proof is elusive and supportive evidence is limited. Methods: Approximately contemporaneous antimicrobial-resistant (n = 181) and antimicrobial-susceptible (n = 159) E. coli isolates from retail meats and from human stool and clinical specimens from a single rural U.S. community were compared for polymerase chain reaction (PCR)-defined phylogenetic group (A, B1, B2, or D) and virulence genotype. Meat and human isolates from the same phylogenetic group with similar virulence profiles underwent sequential two-locus sequence analysis, random amplified polymorphic DNA (RAPD) analysis, and pulsed-field gel electrophoresis (PFGE) analysis. Results: According to phylogenetic distribution, resistant stool isolates were more similar to resistant meat isolates than to susceptible stool isolates. Overall, 19% of meat isolates satisfied molecular criteria for extraintestinal pathogenic E. coli (ExPEC). Nine sequence groups included meat and human isolates, and 17 of these 64 isolates demonstrated >80% RAPD profile similarity to an isolate from the alternate source group (meat vs. human). However, PFGE profiles of the 17 isolates were unique, excepting two stool isolates from the same household. Conclusion: Nearly 20% of meat-source resistant E. coli represented ExPEC. The observed molecular similarity of certain meat and human-source E. coli isolates, including antimicrobial-resistant and potentially pathogenic strains, supports possible foodborne transmission.